Educação física na educação infantil: a organização da prática educativa com bebês em um Centro Municipal de Educação Infantil de Vitória-ES - Valentim, Terezinha Moreira dos Santos (2020)
The present study of a qualitative nature inspired by action research had as its object of study the organization of Educational Practice with babies in a center for early childhood education in the city of Vitória-ES. The central question asked how to organize an educational practice in Physical Education that contemplates and respects the points of view of babies in their experiences in the context of early childhood education, dialoguing with important concepts from the Sociology of Childhood and official curriculum documents focused on early childhood education. The method for data collection was systematic observation with recording in a field diary and photographs. The study points out that in order to carry out a quality early childhood education, a pedagogical intention in the organization and planning of educational practice is essential considering aspects such as affection, constant observation, listening and dialogue with babies, knowledge of their specificities and needs, as well as the partnership with families. In general, the organization of educational practice should start from the babies' points of view placing them at the center of planning and be based on principles consistent with a multicultural curriculum